Direct observation of nodeless superconductivity and phonon modes in electron-doped copper oxide Sr1−xNdxCuO2. Issue 4 (15th December 2021) - Fan, Jia-Qi; Yu, Xue-Qing; Cheng, Fang-Jun; Wang, Heng; Wang, Ruifeng; Ma, Xiaobing; Hu, Xiao-Peng; Zhang, Ding; Ma, Xu-Cun; Xue, Qi-Kun; Song, Can-Li
Abstract: The microscopic understanding of high-temperature superconductivity in cuprates has been hindered by the apparent complexity of crystal structures in these materials. We used scanning tunneling microscopy and spectroscopy to study the electron-doped copper oxide compound Sr1− x Nd x CuO2, which has only bare cations separating the CuO2  planes and thus the simplest infinite-layer structure of all cuprate superconductors. Tunneling conductance spectra of the major CuO2 planes in the superconducting state revealed direct evidence for a nodeless pairing gap, regardless of variation of its magnitude with the local doping of trivalent neodymium. Furthermore, three distinct bosonic modes are observed as multiple peak-dip-hump features outside the superconducting gaps and their respective energies depend little on the spatially varying gaps. As well as the bosonic modes, with energies identical to those of the external, bending and stretching phonons of copper oxides, our findings reveal the origin of the bosonic modes in lattice vibrations rather than spin excitations. Abstract : Tunneling conductance spectra of the essential CuO2 planes in the structurally simplest infinite-layer cuprate superconductors Sr1-x Ndx CuO2 revealed direct evidences for nodeless superconductivity and three lattice vibrational modes.